Application of the 'Luch' Radio Distance Finder - Vorooev,Yu. V. (1973)
Pilot-plant tests of the Luch radio distance finder built in 1969 were successful and in 1970 the distance finder was already in use on the field. The operating qualities of the radio distance finder were more fully revealed under field conditions. In 1970 radio distance finder measurements were made in the Transpolar tundra. Before field work was begun, radio distance measuring stations were comprehensively checked under laboratory conditions; meteorological instruments were standardized; auxiliary equipment was checked. During field operations, scale frequencies were verified (and reduced to the rated values) every two months. A reference standard generator was used to monitor frequencies. Trans. of Geodeziya i Kartografiya (USSR) n9 p24-31 1971.